The Effect of Service Quality on Consumer Satisfaction of Moura Muslim Fashion Boutique in Bandung - Budi Santosa Kramadibrata (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The company is required to implement service quality standard for its products. This study aims to determine the effect of service quality on consumer satisfaction, moslem boutique Moura. This research was conducted using a quantitative approach and associative research design with a total sample of 127 respondents. The instrument used by researchers is questionnaire. Testing the quality of the instrument, namely the validity and reliability. Data analysis using descriptive analysis and correlation. Hypothesis testing using linear regression analysis. The results of this study explain that there is a service quality on customer satisfaction by 31.8%. This analysis is only carried out in one company and does not consider other variables or moderator variables that influence customer satisfaction